КОНЦЕПТУАЛІЗАЦІЯ РЕГРЕСІВ ТА СУБРОГАЦІЇ У СТРАХУВАННІ - Клапків, Юрій Михайлович (Науковий журнал «Світ фінансів», 2017)
Клапків Ю. М. Концептуалізація регресів та суброгації у страхуванні. Охарактеризовано типовий та нетиповий регрес у системі страхування. Представлено особливості типології регресу в майновому страхуванні. З’ясовано різницю між типовим і нетиповим регресом, а також відтворено специфіку вступу в права кредитора, так звану суброгацію, з урахуванням особливих існуючих норм. Висвітлено специфіку страхового регресу на тлі функції страхування цивільної відповідальності. Важливими поняттями, без яких нетиповий регрес не міг би виступати, встановлено умисну вину і разючу недбалість. Виокремлено суброгацію, яку часто абстрагуючи трактують як регрес. На основі юридичних норм ЄС, що дбають про інтереси клієнтів, визначено суть суброгації. Клапкив Ю. М. Концептуализация регрессов и суброгации в страховании. Дана характеристика типичного и нетипичного регресса в системе страхования. Показана типология регресса в имущественном страховании. Изучено разницу между типичным и нетипичным регрессом, представлена специфика вступления в права кредитора, так называемая суброгация, с учетом существующих регуляторних норм. Концептуализирована специфика страхового регресса на фоне функции страхования гражданской ответственности. Установлено, что понятиями, без которых нетипичный регресс не мог бы выступать, является умышленная вина и небрежность. Выделено, суброгацию, которую часто трактуют как регресс. На основе юридических норм ЕС, которые в первую очередь заботятся об интересах клиентов, определена сущность суброгации. Klapkiv Ju. Conceptualization of regression and subrogation in insurance. The article describes characteristics of typical and atypical regression in the insurance system. A typology of regression in property insurance is showed.Introduction. The difference between typical and atypical regression is cleared up. Using of these concepts is a problem. It depends on the interests of the parties.Purpose. Logical separation of regression and subrogation in insurance business is the aim of this research.Results. The specificity of repossession foreclosure is showed as well, subrogation with the special consideration of existing standards. The specificity of insurance regression especially through the functions of liability insurance is explained. The key concepts without which atypical regression could not appear are distinguished. They are deliberate fault and striking negligence. The essence of subrogation which often interpreted as a regression is found. The essence of subrogation is defined on the basis of legal norms of the EU. The main feature that acted as a catalyst instead of concepts regression and subrogation is defined as the concept of period of limitation. However in the case of regression the period of limitation begins from the payment of insurance compensation. In the case of subrogation the period of limitation begins from the realization of the insured event At the same time, the usual recourse claim could not generally be produced to the insurer, as much as it contradicts the liability insurance contract, which should protect him from such liability. The term insurance subrogation conditioned the practice of the European Union where the insurance company is obliged to meet the indemnities’ claims according to the insurance contract and in case when the payment is more than is pointed out in the contract.Conclusion. The insurance company gives the compensation payment and subrogation gives the right to reimburse the paid quota. In developed countries that in the first place care about the interests of the clients. Subrogation takes place when the insurance company helps the client. Regression should take place in Ukraine, giving back compensation by insurance company in case of infraction of contract or by guilty of the damage.